Design, Synthesis, and Herbicidal Activity Evaluation of Novel Aryl-Naphthyl Methanone Derivatives - Fu, Ying; Wang, Kui; Wang, Peng; Kang, Jing-Xin; Gao, Shuang; Zhao, Li-Xia; Ye, Fei (Frontiers in Chemistry, 2019)
4-Hydroxyphenylpyruvate dioxygenase is one of the most vital targets for herbicides discovery. In search for HPPD inhibitors with novel scaffolds, a series of aryl-naphthyl methanone derivatives have been designed and synthesized through alkylation and Friedel-Crafts acylation reactions. The bioassay indicated some of these compounds displayed preferable herbicidal activity at the rate of 0.75 mmol/m2 by post-emergence application, in which compound 3h displayed the best herbicidal activity. The molecular docking showed that the binding pattern of compound 3h with HPPD. This study showed that aryl-naphthyl methanone derivatives could be a potential lead structure for further development of novel herbicides.